Effects of anodisation parameters on thin film properties: a review - Wong Y.H.; Affendy M.G.; Lau S.K.; Teh P.C.; Lee H.J.; Tan C.Y.; Ramesh S. (Taylor and Francis Ltd., 2023)
CMOS integrated circuits; Metallic compounds; Metals; MOS devices; Oxide semiconductors; Temperature; Thin films; Anodisation; Anodising; Applied voltages; Complementary metal oxide semiconductors; Metal oxide film; Nano-structured; Thickness; Thin-film properties; Oxide films